2008
DOI: 10.1182/blood.v112.11.1414.1414
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in Infants with Sickle Cell Anemia: Baseline Data from the BABY HUG Trial.

Abstract: BABY HUG is an NHLBI/NICHD-sponsored Phase III randomized double-blinded placebo-controlled clinical trial (NCT00006400) to test the hypothesis that hydroxyurea can prevent chronic organ damage in very young children with sickle cell anemia (SCA). Renal and splenic function measures are the co-primary endpoints. Renal disease in SCA begins early in life with impaired urine concentration and acidification, along with glomerular hyperfiltration; some patients will progress to microalbuminuria, glomerulosclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Although in the early ages the eGFR values were predominantly normal in this study, evidence of glomerular hyper iltration as suggested by eGFR >140ml/min/1.73m 2 was seen across all the ages from 2-16 years. Similarly, hyper iltration has been seen as early as 9-19 months of age according to the Pediatric Hydroxyurea Phase III Clinical Trial (BABY HUG) study [30]. The compromise of the renal vasculature due to sickled red cells has been associated with glomerular hyper iltration, proteinuria and glomerular hypertrophy.…”
Section: Discusionmentioning
confidence: 99%
“…Although in the early ages the eGFR values were predominantly normal in this study, evidence of glomerular hyper iltration as suggested by eGFR >140ml/min/1.73m 2 was seen across all the ages from 2-16 years. Similarly, hyper iltration has been seen as early as 9-19 months of age according to the Pediatric Hydroxyurea Phase III Clinical Trial (BABY HUG) study [30]. The compromise of the renal vasculature due to sickled red cells has been associated with glomerular hyper iltration, proteinuria and glomerular hypertrophy.…”
Section: Discusionmentioning
confidence: 99%
“…Sickle cell anemia has many complications due to sickle vasoocclusion and hemolytic anemia, and HbF affects the rate of some complications more than others [17]. Table I [18–58] summarizes the relationships HbF concentration with the common complications of disease. High HbF is strongly associated with a reduced rate of acute painful episodes, fewer leg ulcers, and longevity.…”
Section: Hbfmentioning
confidence: 99%
“…Compared with low HbF cases, they had significantly higher minor allele frequencies of the two known trans‐acting elements associated with high HbF (see below), BCL11A and the intergenic interval between HBS1L and MYB (HMIP; 6q22‐23). Individuals with either sickle cell anemia or HbS‐ β 0 thalassemia from the Southwestern Province of Saudi had HbF levels lower that of the individuals from the Eastern Province, yet higher than that of the African American sickle cell patients [77]. Southwestern Province patients have the HbS gene on African HBB haplotypes, usually the Benin type; in contrast to African Americans, they rarely have priapism or leg ulcers [78].…”
Section: Hbfmentioning
confidence: 99%
“…It has proven benefits for the reduction of morbidity and mortality, in both adults and children . Untreated SCA results in significant progressive damage to nearly all organs, most notably the spleen, kidneys, heart, lungs, and brain, beginning as early as the first year of life. With decades of clinical research involving patients with SCA, there is no reason to suggest that hydroxyurea has short‐ or long‐term risks that outweigh its benefits, with improvement noted in nearly all clinical outcomes and even reduced mortality …”
Section: Introductionmentioning
confidence: 99%